The Phenomenon of Digital Transformation of Technology and Communication in School Environments - Parlina, Iin; Ika Purnama Sari (CV. Media Digital Publikasi Indonesia, 2024)
The existence of digital technology tools in today's society is no longer standard, because every society starting from the environment of children's lives, the environment of adolescents and even adults has made technological tools a necessity so that of course it cannot be separated from human life. Many people as individuals in their daily lives and their lives in the organizational environment, digital technology tools play an important role, because all sources of information can be obtained using the help of these technological tools, so that work that has been difficult to complete will become easy and does not take a long time to complete. For students, technological tools are used as a source to find information about science in completing learning tasks that are needed at a certain time. In this community service activity, socialization and training were given to students on how students' behavioral actions in responding to the phenomenon of the transformation of digital technology tools that are used as sources and media for learning. So that digital tools have problems with attacks from technological transformation activities from students' digital tools, they can overcome them. This activity was carried out at the Karalat digitala Private Vocational School in Pematangsiantar City, North Sumatra, with a socialization method provided by the team, and a demonstration of students' work as basic skills training for students in the field of technology by giving several questions at the end of the activity. This was done to measure the level of success in the PkM activity, that the value obtained from several students who answered correctly reached 95.2% who could answer directly from several questions that could be answered by participants (students) of Karalat digital Private Vocational School